Feminist activists on Brexit : from the political to the personal - Cohen, Sue; Page, Margaret (Emerald Publishing Limited, 2021)
Across an ever- changing political landscape, and in the midst of Brexit developments, this edited collection draws our attention to women's participation in transformative democratic processes, and captures how UK women were made 'other' in the political environment created by Brexit. Chronicling the work of diverse feminist activists connected to women's equality organisations, grassroots networks and migrant communities who between them strove to further intersectional equality, and ensure women's voices were heard across the UK during the Brexit campaign, the first section of this book highlights the impact of populist discourses on subjective identities and their place in public and political life. Through reflective conversation, autobiographical writing and poetic pieces, the authors transform their experiences of being 'othered', showcasing instead a new found community and collective agency across intersections of identity. In the second section, researchers and activists analyse how the socio- economic, political and legal changes unleashed by Brexit are undermining women's equality in the UK. Considering how to defend feminist concerns when facing populist political leadership, the authors make the case for constitutional reform which will enable direct female participation in the democratic process. Looking ahead to the post Brexit landscape, and the unknowable future let loose by Covid- 19, the contributors offer us a glimpse of the world they are striving to create.